Greening international aviation post COVID-19 What role for kerosene taxes? - Teusch, Jonas (OECD Taxation Working Papers, 2021)
This paper discusses the contribution that kerosene taxes could make to decarbonising international air travel post COVID-19. Reaching climate neutrality by mid-century requires that all sectors, including aviation, cut emissions strongly. The paper argues that clarity on decarbonisation targets, including through carbon price signals in the form of kerosene taxes, will support an orderly transition in aviation. A gradually increasing tax on kerosene can strengthen the incentives for investment and innovation in clean aviation technologies. Taxing kerosene would also provide implementing countries with tax revenues that could be used to support clean investment and innovation, while addressing competitiveness and equity issues. Where legal obstacles to taxing kerosene exist, these can be overcome by renegotiating the relevant air service agreements